The delay loop phenomenon in high temperature elasticity modulus test by in-situ ultrasonic measurements. (August 2020) - Xue, Huan; Liu, Dong; Ge, Rui; Pan, Libo; Peng, Wenjie
Highlights: A delay loop phenomenon is found in the in-situ ultrasonic elastic modulus test. The feedback temperature delay is the possible reason of this phenomenon. Traditional single process method will introduce a non-negligible error. The cycle average method is a feasible correction method. Abstract: The static and dynamic elastic modulus evaluation methods at high temperature are introduced and compared. The in-situ ultrasonic pulse-echo method is used to assess the high temperature physical performance of pressure vessel steel 7Cr2AlMoRe. The results show when the temperature arises from 20 °C to 800 °C, the elasticity modulus decreases from 217 GPa to 150 GPa. A delay loop phenomenon is found in the test that the in-situ elastic modulus values in the heating process are higher than the values in the cooling process at the same temperature point, which forms a loop in the whole process. A contrast test is carried out on the 304 stainless steel at the same experimental settings. The result shows the delay loop of stainless steel is wider than that of 7Cr2AlMoRe as the thermal conductivity of stainless steel is about 40% of the carbon steel. It indicates that the feedback temperature delay is the possible reason of this phenomenon. Only one heating up process test will introduce a non-negligible error, taking the average value at the same temperature point in heating up and cooling down process is a feasible correction method.